Transient asymptomatic white matter lesions following Epstein-Barr virus encephalitis - Yoon Young Jang; Kye Hyang Lee (Korean Pediatric Society, 2011)
We present the case of a patient with Epstein-Barr virus (EBV) encephalitis who developed abnormal white matter lesions during the chronic phases of the infection. A 2-year-old-boy was admitted for a 2 day history of decreased activity with ataxic gait. The results of the physical examination were unremarkable except for generalized lethargy and enlarged tonsils with exudates. Brain magnetic resonance imaging (MRI) at admission showed multiple high signal intensities in both basal ganglia and thalami. The result of EBV polymerase chain reaction (PCR) of the cerebral spinal fluid was positive, and a serological test showed acute EBV infection. The patient was diagnosed with EBV encephalitis and recovered fully without any residual neurologic complications. Subsequently, follow-up MRI at 5 weeks revealed extensive periventricular white matter lesions. Since the patient remained clinically stable and asymptomatic during the follow-up period, no additional studies were performed and no additional treatments were provided. At the 1-year follow-up, cranial MRI showed complete disappearance of the abnormal high signal intensities previously seen in the white matter. The patient continued to remain healthy with no focal neurologic deficits on examination. This is the first case of asymptomatic self-limited white matter lesions seen in serial MRI studies in a Korean boy with EBV encephalitis.